Some Recent Studies of American Church History - Brock, W. R. (The journal of ecclesiastical history, 1978)
In a little over 400 pages Robert T. Handy's volume of the Oxford History of the Christian Church surveys more than four hundred years, two countries of vast geographical extent, almost 300 million people, fifteen churches claiming over two million members each, innumerable smaller churches, denominations and sects. One cannot but admire the tenacity with which he has carried out this daunting task, and be grateful for a critical bibliography of over 30 pages which will be invaluable for anyone who requires a quick guide to the literature on almost any aspect of American or Canadian Church history. The presentation is clear, and the stream—or torrent—of information is handled with skill.